Risk factors for hidradenitis suppurativa: a pilot study - Schmitt, Juliano Vilaverde [UNESP]; Bombonatto, Giovana; Martin, Manoela; Miot, Hélio Amante [UNESP] (Sociedade Brasileira de Dermatologia, 2012)
A hidradenite supurativa é uma doença inflamatória crônica debilitante de etiologia parcialmente compreendida. Realizamos um estudo piloto tipo caso-controle pareado por sexo e idade com outros pacientes dermatológicos para analisar prováveis fatores de risco associados a esta doença. Incluímos 15 casos e 45 controles, sendo 67% mulheres. Análise bivariada e multivariada por regressão logística identificou associação significativa com tabagismo, índice de massa corporal mais elevado e história familiar. O uso de contraceptivos hormonais foi menos frequente nas portadoras de hidradenite.

The hidradenitis suppurativa is a chronic debilitating inflammatory disease whose etiology is not fully understood. We conducted a pilot case-control study matched by sex and age with other dermatological patients to analyze possible risk factors associated with this disease. We included 15 cases and 45 controls, 67% were women. Bivariate and multivariate logistic regression analysis identified significant association with smoking, higher body mass index and family history. The use of hormonal contraceptives was less frequent in women with hidradenitis.
Fatores de risco para hidradenite supurativa: um estudo piloto
Keywords: Fatores de risco; Hidradenite supurativa; Obesidade; Tabagismo; Hidradenitis suppurativa; Obesity; Risk factors; Smoking